2002
DOI: 10.1162/08989290260045819
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differentiation of Lexico-Syntactic Categories or Semantic Features? Event-Related Potential Evidence for Both

Abstract: Event-related potentials (ERPs) were used to investigate whether processing differences between nouns and verbs can be accounted for by the differential salience of visual-perceptual and motor attributes in their semantic specifications. Three subclasses of nouns and verbs were selected, which differed in their semantic attribute composition (abstract, high visual, high visual and motor). Single visual word presentation with a recognition memory task was used. While multiple robust and parallel ERP effects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 78 publications
7
64
1
Order By: Relevance
“…However, strikingly, no frontal concreteness effects emerged for syntactically and semantic ambiguous items used as verbs (AA-V). Thus, similar to the Kellenbach et al (2002) findings in German, a morphologically rich language in which word class ambiguity (and associated semantic ambiguity) is unlikely, we find that verbs in English do manifest concreteness effects, as long as they are not semantically ambiguous. The response to the semantically ambiguous verbs in the present study was, however, similar to that observed more globally to Chinese verbs in Zhang et al's (2006) study, in that the AA-V items elicited concreteness effects that were limited to posterior channels in the N400 time window.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, strikingly, no frontal concreteness effects emerged for syntactically and semantic ambiguous items used as verbs (AA-V). Thus, similar to the Kellenbach et al (2002) findings in German, a morphologically rich language in which word class ambiguity (and associated semantic ambiguity) is unlikely, we find that verbs in English do manifest concreteness effects, as long as they are not semantically ambiguous. The response to the semantically ambiguous verbs in the present study was, however, similar to that observed more globally to Chinese verbs in Zhang et al's (2006) study, in that the AA-V items elicited concreteness effects that were limited to posterior channels in the N400 time window.…”
Section: Discussionsupporting
confidence: 84%
“…Given that there are suggestions of multiple subcomponents of the ERP concreteness effect, it is further possible that different aspects of the response (e.g., the N400 and the slow frontal negativity) may be differentially sensitive to these factors, allowing these subcomponents to be more definitively separated. Finally, the differences in the results of the Kellenbach et al (2002) and the Zhang et al (2006) studies for concreteness effects on verbs, seen across languages that vary in degree of lexical ambiguity, leads to the specific prediction that concreteness effects for verbs in the present study may be more sensitive to ambiguity than concreteness effects for nouns.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Several studies using ERP methodology with a focus on the N400 component have revealed wave-form related differences associated with differences in semantic or grammatical category membership or with differences in orthographic properties, distinguishing between concrete versus abstract words (Paz-Caballero and Menor, 1999), nouns versus verbs (Pulvermüller et al, 1999;Kellenbach et al, 2002), items having high versus low numbers of orthographic neighbors (Holcomb et al, 2002). On the specific subject of the natural/artifactual dissociation, Kiefer (2001), using a superordinate object categorization task, found that the topographic distribution of the N400 component varied as a function of domain.…”
Section: Introductionmentioning
confidence: 99%